2019
DOI: 10.1590/0100-5405/187102
|View full text |Cite
|
Sign up to set email alerts
|

Cama de aviário e solo não autoclavados são eficientes no controle do crescimento de Scytalidium lignicola, causador da podridão negra da mandioca

Abstract: RESUMO A podridão negra da mandioca causada por Scytalidium lignicola vem se tornando uma doença importante para os estados produtores devido a grandes perdas de produção. Por isso o objetivo do presente trabalho foi avaliar o efeito de fontes e doses de matéria orgânica isolada e adicionada a solo arenoso sob a supressividade do crescimento micelial de S. lignicola CMM 1098. Foram realizados dois experimentos o primeiro foi visando avaliar o efeito dos extratos de materiais orgânico (cama de aviário, esterco … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…The suppression of diseases caused by soil-borne pathogens is closely intertwined with enzyme activities. Bezerra et al (2019) showed that natural suppression of cassava black root rot has been found correlated with arylsulfatase and urease activities. Numerous researchers have observed that integrating biochar into the soil shows potential in mitigating crop diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The suppression of diseases caused by soil-borne pathogens is closely intertwined with enzyme activities. Bezerra et al (2019) showed that natural suppression of cassava black root rot has been found correlated with arylsulfatase and urease activities. Numerous researchers have observed that integrating biochar into the soil shows potential in mitigating crop diseases.…”
Section: Introductionmentioning
confidence: 99%